2013
DOI: 10.2334/josnusd.55.157
|View full text |Cite
|
Sign up to set email alerts
|

Mycological and histological associations of Candida in oral mucosal lesions

Abstract: The present study aimed to assess the presence and level of colonization of Candida in patients with oral mucosal lesions, to determine the presence or absence of candidal hyphae in biopsy specimens and to correlate the degree of epithelial dysplasia with the number of colony-forming units of Candida. We performed a prospective study including 50 patients diagnosed as having oral potentially malignant and malignant disorders. These patients had lesions such as leukoplakia, lichen planus, lichenoid reaction, ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Three decades ago, Krogh's group assessed the nitrosation potential of Candida strains isolated from oral leukoplakia lesions, and found strains with high potential for nitrosation to be associated with greater levels of dysplasia [88]. A series of studies published between 1994 and 2013 used periodic Acid-Schiff (PAS) staining and cultivation techniques to detect/isolate yeasts in mucosal swabs or biopsies of oral dysplasia or OSCC [89][90][91][92][93]. Two studies also performed culturing and counting of colony-forming unit (CFU) in oral rinse samples [91,93].…”
Section: The Mycobiome Associated With Oral Cancermentioning
confidence: 99%
“…Three decades ago, Krogh's group assessed the nitrosation potential of Candida strains isolated from oral leukoplakia lesions, and found strains with high potential for nitrosation to be associated with greater levels of dysplasia [88]. A series of studies published between 1994 and 2013 used periodic Acid-Schiff (PAS) staining and cultivation techniques to detect/isolate yeasts in mucosal swabs or biopsies of oral dysplasia or OSCC [89][90][91][92][93]. Two studies also performed culturing and counting of colony-forming unit (CFU) in oral rinse samples [91,93].…”
Section: The Mycobiome Associated With Oral Cancermentioning
confidence: 99%
“…There are conflicting results regarding the association of leukoplakia and human papillomavirus (HPV) infection [6,8]. The role of torque teno virus (TTV) [9,10], Epstein-Barr virus (EBV) [11] and Candida albicans [8,[12][13][14][15][16] in leukoplakia development and carcinogenesis remains to be clarified, too. Additionally, it has been also demonstrated that specific bacterial infections like Helicobacter pylori [17] or the intracellular Mycoplasma salivarium [18] could also be involved in this process.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that epithelial dysplasia is one of the most important indicators of potential malignancy (6). Generally, nonhomogeneous lesions or pure erythroplakia have a higher risk than lesions with a homogenous appearance (8). Lesions on the tongue or floor of the mouth also have a higher potential for malignancy.…”
Section: Discussionmentioning
confidence: 99%